Using an inclusive therapeutic theatre production to teach self-advocacy skills in young people with disabilities. (November 2020) - Cook, Angelle
Highlights: therapeutic theatre interventions may be one way to teach the self advocacy skill of assertiveness to individuals with disabilities Those with disabilities may find a need self advocate because of living within an ableist world. Role play assessments may be one type of measurement to utilize for those with disabilities. Abstract: This quantitative study utilized an inclusive therapeutic theatre production for young people with disabilities, mental illness, and medical conditions to establish if involvement in the production could affect self-advocacy skills, specifically, assertiveness. In the literature, assertiveness has been documented as a subcomponent of self-advocacy. The therapeutic theatre intervention thematically centered on the characters advocating for their needs. The Drama Therapy Role Play Interview (DTRPI), an established role-play measure developed by Snow (2009) for participants with disabilities, was used as the pre- and post-test measure.  A single-sample t -test was conducted to determine if any difference existed between the pre-test and post-test scores for assertiveness.  The participants scored significantly higher in the post-test ( M = .88, SD = .92) than in the pre-test t (12) = (3.48), p = 0.005. The agent of change could have been achieved through several means: education, discussion, or embodiment.